Maternal satisfaction on quality of childhood vaccination services and its associated factors at public health centers in Addis Ababa, Ethiopia - Eyasu Tesfaye; Ayal Debie; Fasil Sisay; Tesfahun Zemene Tafere (BMC, 2023)
Abstract Background Vaccination is one of the most important public health interventions to reduce child mortality and morbidity. In Ethiopia, about 472,000 children die each year by vaccine-preventable diseases. A satisfied mother is assumed to use the services and complies with the service provider for better health care outcomes. However, there was no adequate evidence regarding maternal satisfaction with quality of childhood vaccination services. This study aimed to assess maternal satisfaction on quality of childhood vaccination services and its associated factors at public health centers in Addis Ababa, Ethiopia. Methods A facility-based cross-sectional study was conducted from 12 July to 12 August 2021 at public health centers in Addis Ababa, Ethiopia. A total of 366 mothers (caretakers) of under one-year-old children participated in the study. A systematic sampling technique with an interviewer-administered questionnaire and inventory checklist were used to collect the data. A binary logistic regression model was fitted. Adjusted Odds Ratio (AOR) with 95% confidence interval (CI) and p-value < 0.05 were used to identify the factors associated with the outcome. Results Nearly two-thirds (61.2%) of mothers (caretakers) were satisfied with the quality of childhood vaccination services. Service providers' greeting [AOR = 1.60; 95%CI: 1.37-1.99] and information about the types of vaccines [AOR = 1.54; 95%CI: 1.32-1.89] were positively associated with maternal satisfaction. On the contrary, long waiting time of mothers (caretakers) to receive services [AOR = 0.29; 95%CI: 0.14-0.62] was negatively associated with services. Conclusion The overall maternal satisfaction towards the quality of childhood vaccination services in this study was found to be low. Minimizing waiting time at the health facility, enhancing greetings and providing adequate information regarding childhood vaccination for mothers (caretakers) improved their satisfaction with the services.